Matlab Simulation of Single-Phase Reconfigurable Inverter Topology for a Solar Powered Hybrid AC/DC Home Appliances: Advancements in Inverter Technology for Solar Powered Homes (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this paper modelling, simulation and control of grid tie PV system using multilevel inverter are described. The majority of PV systems require inverters as interfacing units. A reconﬁgurable single phase inverter topology for a hybrid acdc solar powered home is suggested here. This inverter possesses a single-phase single-stage topology and the main advantage of this converter is that it can perform dcdc, dcac, and grid tie operation, thus reducing loss, cost, and size of the converter. This hybrid acdc home has both ac and dc appliances. This type of home helps to reduce the power loss by avoiding unnecessary double stages of power conversion and improves the harmonic proﬁle by isolating dc loads to dc supply side and rest to ac side. Simulation is done in MATLABSimulink and the obtained results are validated through hardware implementation using Arduino Uno controller. Such type of solar powered home equipped with this novel inverter topology could become a basic building block for future energy efficient smart grid and micro grid.